Study of the operation of the output filter of a single-phase series active power filter - Mihail Antchev; Vanjo Gourgoulitsov; Hristo Antchev (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In the article is presented a single-phase series active power filter (SFSAPF) designed to compensate the total harmonic distortion (THD) factor of the supply network voltage. Particular attention is paid to the work of the output capacitor of the passive filter, and dependencies for the design of the filter at hysteresis voltage control are presented. The value of the higher harmonics of the current through the filter capacitor is determined. A mathematical relationship between the voltage ripple of the capacitor, its value and the switching frequency is derived. As a result of the advanced research a methodology for designing the output filter of a single-phase serial active power filter has been proposed. The results from computer simulation and experiment are also given.